Hype or hope – Can combination therapies with third-generation EGFR-TKIs help overcome acquired resistance and improve outcomes in EGFR-mutant advanced/metastatic NSCLC?. (October 2021) - Papini, Filippo; Sundaresan, Janani; Leonetti, Alessandro; Tiseo, Marcello; Rolfo, Christian; Peters, Godefridus J.; Giovannetti, Elisa
Abstract: Three generations of epidermal growth factor receptor - tyrosine kinase inhibitors (EGFR-TKIs) have been developed for treating advanced/metastatic non-small cell lung cancer (NSCLC) patients harboring EGFR- activating mutations, while a fourth generation is undergoing preclinical assessment. Although initially effective, acquired resistance to EGFR-TKIs usually arises within a year due to the emergence of clones harboring multiple resistance mechanisms. Therefore, the combination of EGFR-TKIs with other therapeutic agents has emerged as a potential strategy to overcome resistance and improve clinical outcomes. However, results obtained so far are ambiguous and ideal therapies for patients who experience disease progression during treatment with EGFR-TKIs remain elusive. This review provides an updated landscape of EGFR-TKIs, along with a description of the mechanisms causing resistance to these drugs. Moreover, it discusses the current knowledge, limitations, and future perspective regarding the use of EGFR-TKIs in combination with other anticancer agents, supporting the need for bench-to-bedside approaches in selected populations.